Mountain Tourism Workforce's Resilience During COVID Pandemic (Journal of Tourism and Himalayan Adventures, 2023)
Nepal is a home to different famous mountains including Mount Everest, the highest mountain of the planet. The geography of Nepal is both an opportunity and a threat to the country and the communities. More than 15 percent of land lies in mountainous regions where tourism is the major profession to rely on for the communities. However, the region encountered one of the greatest threats in the form of COVID-19 which restricted people's mobility. The livelihood of the mountain communities which are directly or indirectly dependent on tourism was severely affected by COVID-19. The prime trait that helped minimize the damage was the resilience of the mountain community. This qualitative study attempts to assess the resilience (community resilience) of mountain people with the cases from the Everest and Annapurna region and analyze it against the theory of resilience.